SIMULASI ARUS LALU LINTAS DENGAN MENGGUNAKAN KECEPATAN MODEL KERNER KONHÃUSER - Yusnita, Yessy (DIMENSI, 2016)
In the real situation, the vehicle flow velocity on a road are not always in an equilibrium situation. The Kerner KonhÃ¤user model illustrate that the vehicle flow velocity is an application of the Navier Stokes equation. The model is solved numerically by using the finite difference approach to calculate the flow velocity. The result will be used in solve the conservation equations in order to the density of traffic flow. The Simulation is carried on a single-lane road section. The results show that the vehicle flow velocity will increase if the density of the traffic flow decreases and the vehicle flow velocity will decrease if the density of traffic flow increases.